New syllabus primary Mathematics 5 - Yee , Foong Pui; Brandon Oh; Lin Li Gek Pearlyn (Karachi : Oxford university press, 2019)
The Primary Mathematics 5 syllabus is designed to provide students with a solid foundation in mathematics. Here's a brief summary of the key topics typically covered: 1-Number Sense: 2-Geometry: 3-Measurement: 4-Data Handling: 5- Patterns and Algebra: 6- Problem-Solving.
Keywords: Mathematics -Text Book 5; Oxford Mathematics book 5